Sex differences in APOE- and PICALM-related cognitive profiles in healthy middle-aged adults - Bednorz, Adam; Trybek, Paulina; Hoang, Minh Tuan; Religa, Dorota (Frontiers in Aging, 2026)
IntroductionThe APOEε4 and PICALM GG genotypes are strong genetic risk factors for Alzheimer’s disease. This study aimed to identify cognitive subgroups using unsupervised machine learning and to investigate the influence of APOE and PICALM genotypes on cognitive performance.Material and methodsCognitive, genetic and demographic data from 192 healthy middle-aged adults (50–63 years) from the PEARL-Neuro Database were analyzed using agglomerative hierarchical clustering. Neuropsychological tests included the California Verbal Learning Test, Raven’s Progressive Matrices, and the Edinburgh Handedness Inventory. Subsequent analyses used linear regression models to assess the effects of APOE, PICALM, and their interaction on cognitive outcomes.ResultsTwo cognitive subgroups (better vs. worse performance) were identified for both females (n = 60/43) and males (n = 38/51). In women with lower cognitive performance, the presence of the APOEε3ε4 allele was significantly associated with a higher number of perseverations (CVLT9: pFDR=0.02, R2=0.18) and lower recognition accuracy (CVLT12: pFDR=0.04, R2=0.12). A significant PICALM GG× education interaction was observed for fluid intelligence (pFDR=0.03, R2=0.34). In men with lower cognitive performance, the APOEε3ε4 genotype was associated with lower fluid intelligence scores (RPM: pFDR=0.04, R2=0.09). Furthermore, significant APOE×PICALM interactions were found for verbal learning (CVLT1: pFDR=0.03, R2=0.16) as well as delayed cued recall (CVLT6: pFDR=0.03, R2=0.12; CVLT8: pFDR=0.03, R2=0.13).ConclusionThis study revealed significant sex differences in gene–cognition interactions. In females with lower cognitive performance, the genotype APOEε3ε4 was associated with poorer recognition, while the combined effects of APOE×PICALM in males were associated with weaker episodic memory. Although performance remained within normative ranges, these subtle differences may indicate early risk and warrant longitudinal monitoring.